Reply to the Letter to the Editor. Regarding the Paper "Stable Eutectoid Transformation in Nodular Cast Iron: Modeling and Validation" F. D. Carazo, P. M. Dardati, D. J. Celentano, and L. A. Godoy: MMTA 2017 - Carazo, Fernando Diego (2017)
Respuesta a una carta al Editor del Journal o discusión planteada por el Prof. Jacques Lacaze al artículo de mi autoría "Stable eutectoid transformation in nodular cast iron: modeling and validation" (DOI: http://dx.doi.org/10.1007/s11661-016-3827-6)